Snake envenoming: a disease of poverty. - Robert A Harrison; Adam Hargreaves; Simon C Wagstaff; Brian Faragher; David G Lalloo (Public Library of Science (PLoS), 2009)
Background Most epidemiological and clinical reports on snake envenoming focus on a single country and describe rural communities as being at greatest risk. Reports linking snakebite vulnerability to socioeconomic status are usually limited to anecdotal statements. The few reports with a global perspective have identified the tropical regions of Asia and Africa as suffering the highest levels of snakebite-induced mortality. Our analysis examined the association between globally available data on snakebite-induced mortality and socioeconomic indicators of poverty. Methodology/principal findings We acquired data on (i) the Human Development Index, (ii) the Per Capita Government Expenditure on Health, (iii) the Percentage Labour Force in Agriculture and (iv) Gross Domestic Product Per Capita from publicly available databases on the 138 countries for which snakebite-induced mortality rates have recently been estimated. The socioeconomic datasets were then plotted against the snakebite-induced mortality estimates (where both datasets were available) and the relationship determined. Each analysis illustrated a strong association between snakebite-induced mortality and poverty. Conclusions/significance This study, the first of its kind, unequivocally demonstrates that snake envenoming is a disease of the poor. The negative association between snakebite deaths and government expenditure on health confirms that the burden of mortality is highest in those countries least able to deal with the considerable financial cost of snakebite.